1997
DOI: 10.1136/gut.41.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of transforming growth factor α precursors in acute experimental colitis in rats

Abstract: Background and aim-Epidermal growth factor (EGF) and transforming growth factor (TGF-), members of the EGF family of growth factors, protect rat gastric and colonic mucosa against injury. Having shown previously that exogenously applied EGF protects rat colonic mucosa against injury, the aim of the present study was to evaluate the endogenously expressed ligand mediating the protective eVect of EGF/TGF-in vivo. Methods-In an experimental model of trinitrobenzene sulphonic acid (TNBS)/ ethanol induced colitis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
25
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 39 publications
9
25
0
1
Order By: Relevance
“…Recently, Hoffman and colleagues have also identified only the precursor forms of TGF-␣ in an acute model of experimental colitis in rats. They propose that the absence of the mature peptide may be due to its rapid removal from the lumen of the inflamed intestine (52). The absence of the mature protein in our ex vivo organ culture supernatants lends further support to their observations that the precursor forms of TGF-␣ may be the true ligands for the EGFR during episodes of inflammation.…”
Section: Discussionsupporting
confidence: 66%
“…Recently, Hoffman and colleagues have also identified only the precursor forms of TGF-␣ in an acute model of experimental colitis in rats. They propose that the absence of the mature peptide may be due to its rapid removal from the lumen of the inflamed intestine (52). The absence of the mature protein in our ex vivo organ culture supernatants lends further support to their observations that the precursor forms of TGF-␣ may be the true ligands for the EGFR during episodes of inflammation.…”
Section: Discussionsupporting
confidence: 66%
“…The two larger molecular species probably represent precursor peptides of TGF-␣ which were also shown in some previous studies (Hansard et al 1997;Hoffmann et al 1997;Tureaud et al 1997;Wang et al 1997). Using this antibody, no TGF-␣ immunoreactivity was found in colon protein samples from knockout mice ( Figure 3A, Lane 4), but one band of around 25-28 kD was revealed in the sample from wild-type mice ( Figure 3A, Lane 5).…”
Section: Western Immunoblotting For Antibody Specificity Analysismentioning
confidence: 78%
“…However, scarce reports exist about the regulation of TGFA expression in the mucosa [57]. Several studies reported a rapid induction of TGFA expression in models of gut inflammation and mucosal injury [58][59][60][61], suggesting a potential relevance for TGFA in weaning-associated inflammation. Recently, TGFA expression was studied in colon and duodenum during postnatal development in rats [62,63], but to our knowledge this is the first study profiling postnatal TGFA expression in distal small intestine in pigs.…”
Section: Discussionmentioning
confidence: 99%